2003
DOI: 10.1021/jf034954v
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Related Compounds and Lignans in Prunes (Prunus domestica L.) and Their Oxygen Radical Absorbance Capacity (ORAC)

Abstract: Four new abscisic acid related compounds (1-4), together with (+)-abscisic acid (5), (+)-beta-D-glucopyranosyl abscisate (6), (6S,9R)-roseoside (7), and two lignan glucosides ((+)-pinoresinol mono-beta-D-glucopyranoside (8) and 3-(beta-D-glucopyranosyloxymethyl)-2- (4-hydroxy-3-methoxyphenyl)-5-(3-hydroxypropyl)-7-methoxy-(2R,3S)-dihydrobenzofuran (9)) were isolated from the antioxidative ethanol extract of prunes (Prunus domestica L.). The structures of 1-4 were elucidated on the basis of NMR and MS spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…The plum fruit is a good source of vitamins, minerals, fiber and enzymes that are good for the digestive system and positively associated with nutrient intake, improves anthropometric measurements; the prune is a useful antistresser (Hiramoto, 2008) and reduces risk of hypertension (Beals and Fulgoni, 2005;Ahmed et al, 2010a). Besides various sugars, acids, pectins, tannins and enzymes, European plum fruits also contain several important secondary metabolites such as flavonoids and phenolic acids (Tomas-Barberan et al, 2001;Gil et al, 2002;Walkowiak-Tomczak et al, 2008;Slimestad et al, 2009), with a strong antioxidant capacity (Kahkonen et al, 1999;Nakatani et al, 2000;Vinson et al, 2001;Kayano et al, 2002Kayano et al, , 2003Kayano et al, , 2004Kikuzaki et al, 2004;Kimura et al, 2008;Rop et al, 2009;Dhingra et al, 2014). Ascorbic acid is another antioxidant present in plum fruit, essential for higher primates and a small number of other species (Gil et al, 2002).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…The plum fruit is a good source of vitamins, minerals, fiber and enzymes that are good for the digestive system and positively associated with nutrient intake, improves anthropometric measurements; the prune is a useful antistresser (Hiramoto, 2008) and reduces risk of hypertension (Beals and Fulgoni, 2005;Ahmed et al, 2010a). Besides various sugars, acids, pectins, tannins and enzymes, European plum fruits also contain several important secondary metabolites such as flavonoids and phenolic acids (Tomas-Barberan et al, 2001;Gil et al, 2002;Walkowiak-Tomczak et al, 2008;Slimestad et al, 2009), with a strong antioxidant capacity (Kahkonen et al, 1999;Nakatani et al, 2000;Vinson et al, 2001;Kayano et al, 2002Kayano et al, , 2003Kayano et al, , 2004Kikuzaki et al, 2004;Kimura et al, 2008;Rop et al, 2009;Dhingra et al, 2014). Ascorbic acid is another antioxidant present in plum fruit, essential for higher primates and a small number of other species (Gil et al, 2002).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…From these data together with further HMBC correlations between H-4 000 (d H 8.03) and C-8 000 , H-5 00 (d H 6.48) and C-1 000 , H 3 -6 00 (d H 2.12) and C-2 00 (d C 119.5) and C-4 00 (d C 133.1), and those shown in Fig. 2, the structure of the acid moiety was expected to be a derivative of abscisic acid with a c-lactone ring, which comprised 15 carbon atoms and was first isolated from Prunus domestica in an acid form (16) [15] ( Table 1). The position of the ester linkage was confirmed to be on the hydroxy group at C-6 0 by the correlation peak between H 2 -6 0 (d H 4.39 and 4.35) and C-1 0 (d C 167.3) in the HMBC spectrum.…”
Section: Resultsmentioning
confidence: 95%
“…It was indicated that this ester group was derived through the oxidization of a CH 2 group in the bicyclic sesquiterpene moiety of thorelinin. Hence, the sesquiterpene moiety was identified as ( [7]. The upfield shift of the ester C(1)¼O C-atom in 1 and the HMBC from CH 2 (6'') to C(1) suggested the linkage of the sesquiterpene and sugar moiety via an ester bond.…”
Section: Results Andmentioning
confidence: 98%
“…They were (À)-lyoniresinol (3) [10] [14], ssioriside (9) [15], glochidioboside (10) [16], and [(2R,3S)-2,3-dihydro-2-(4-hydroxy-3-methoxyphenyl)-5-(3-hydroxypropyl)-7-methoxy-1-benzofuran-3-yl]methyl b-d-glucopyranoside (11) [7]. In the previous studies, four types of lignans, viz., ditetrahydrofuran, tetrahydrofuran, benzofuran, and biphenyl, were reported from plants of the Litsea genus.…”
Section: Results Andmentioning
confidence: 99%